PENGARUH KEPERCAYAAN (TRUST), BELANJA ONLINE DAN GAYA HIDUP TERHADAP KEPUASAN KONSUMEN YANG BERDAMPAK PADA LOYALITAS PENGGUNA PLATFORM E-COMMERCE SHOPEE PADA KALANGAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Farisi, Jufair; Subaida, Ida; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Marketing is a dynamic field that hinges on the relationship between companies and consumers. In today's fast-paced world, companies must constantly adapt to the latest trends in product marketing. This research is of significant importance as it aims to delve into the influence of Trust, Online Shopping, and Lifestyle on Consumer Satisfaction, thereby impacting user Loyalty. The target respondents for this research were students from the economics and business faculty at Universitas Abdurachman Saleh Situbondo, selected using a simple random sampling method. The data analysis and hypotheses were conducted using the Partial Least Square-Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the smart PLS 3.0 application show that Trust has a significant effect on consumer satisfaction, Online shopping has a significant effect on consumer satisfaction, Lifestyle has a significant effect on consumer Satisfaction, Trust has a positive and insignificant effect on user Loyalty, Online shopping has a significant positive effect on user Loyalty, Lifestyle has no significant effect on user Loyalty, consumer Satisfaction has no significant effect on user Loyalty. The indirect influence hypothesis test results show that Trust has no significant effect on user Loyalty through consumer Satisfaction, Online shopping has no significant effect on user Loyalty through consumer Satisfaction, and Lifestyle has no significant effect on user Loyalty through consumer Satisfaction.